(untitled) (Bangladesh Journal of Psychiatry, 2018)
Schizophrenia is a chronic psychiatric illness with high rate of relapse which is commonly associated with noncompliance of medicine, as well as stress and high expressed emotions. The objective of the study was to determine the factors of relapse among the schizophrenic patients attending in outpatient departments of three tertiary level psychiatric facilities in Bangladesh. This was a cross sectional study conducted from July, 2001 to June, 2002. Two hundred patients including both relapse and nonrelapse cases of schizophrenia and their key relatives were included by purposive sampling. The results showed no statistically significant difference in terms of relapse with age, sex, religion, residence, occupation and level of education (p>0.05), but statistically significant difference was found with marital status and economic status (p<0.01). The proportion of non-compliance was found to be 80% and 14%, of high expressed emotion was 17% and 2% and of the occurrence of stressful life events was 10% and 1% in relapse and non-relapse cases respectively which were statistically significant (p<0.001). The study indicated that stressful life events, high expressed emotion, and noncompliance with medication had a role in schizophrenic patients for its relapse. Bang J Psychiatry December 2015; 29(2): 59-63